ARHIVAREA ELECTRONICĂ ÎN BIBLIOTECILE UNIVERSITARE - USM ADMIN (Studia Universitatis Moldaviae: Stiinte Sociale, 2012)
The article is devoted to the international movement Open Access (OA) to scientific knowledge, where the academic libraries have an important role. The purpose of the libraries is to provide institutional digital repositories, to ensure quality metadata and the security and stability of materials. The library implements ideas of Open Access and actively promotes the benefits of electronic archives among the researchers. The libraries actively participate in creation and maintenance of open electronic archives; contribute to the publication of OA journals. The journals and open access institutional deposits are considered today a new model of scientific communication.